Analisa Hasil Forensik Penerapan Manajemen Waktu pada Proyek Jalan Di Ruas Rancapanggung – Sarinagen Kabupaten Bandung Barat - Nurwahyono; Antono Damayanto (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2024)
Time management is a crucial process to ensure projects are completed on time, which focuses on planning and scheduling project activities to make them faster and more efficient. This research explores the application of time management in the Road construction project in Rancapanggung - Sarinagen, West Bandung Regency, implemented by PT Basuki - Lesindo, KSO. The purpose of this study is to identify and understand the factors that hinder time management and the dominant factors that influence it. The research method used a quantitative approach through questionnaires to 21 respondents, followed by descriptive analysis and ranking of respondents, and validation through interviews. The results showed four main barriers in the implementation of time management, insufficient number of work tools (dominant factor with 44.5%), inappropriate construction methods (43%), lack of communication and coordination among the project implementation team (41.5%), and materials that are damaged or not according to specifications (41.4%). The most dominant factor in the delay was the insufficient number of work tools, indicating the importance of adequate resource allocation.